Formulation and evaluation of SPAN-60-based valacyclovir proniosomal gel for ocular delivery - Nyanbeni Y Kikon; Shalu Verma; Nidhi Gairola; Alka Singh; Tarun Parashar (Journal of Applied Pharmaceutical Research, 2026)
Background: Ocular administration is a challenging route of drug delivery due to the eye's distinct anatomy and physiology. Valacyclovir is commonly prescribed to treat viral ophthalmological conditions. However, its poor permeability limits its effectiveness in ocular viral infections. In this study, valacyclovir proniosomal gels (F1-F14) have been prepared for ocular permeation. Methodology: The VCV proniosomal gel was prepared using varying ratios of cholesterol, Span 60, and lecithin via coacervation-phase separation. The prepared proniosomal gels were characterized for particle size and shape, viscosity, drug entrapment efficiency (EE%), surface morphology, zeta potential, and in vitro drug release. Result and Discussion: Data from experimentation indicate that all formulations prepared were found to have high entrapped efficiency (%), with the highest value being (90.70%) for F7. The final formulation showed a ZP of -27.40 ± 2 mV, a PDI of 0.231, and a vesicle size of 64.31 nm, indicating uniformly dispersed, nanosized vesicles well-suited for ocular drug delivery and exhibiting greater colloidal stability. Conclusion: The results from all fourteen formulations of in vitro drug release demonstrated that they all released their drug in a sustained manner for at least 10 hours following release. The patterns of drug release from the in vitro tests fitted into the Korsmeyer–Peppas model of drug release kinetics. Overall, the results show that using VCV in a proniosomal form enables prolonged, enhanced corneal permeation.